2021
DOI: 10.3390/cancers13050938
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Features Differentiating Follicular Thyroid Cancer from Follicular Adenoma–A Meta-Analysis

Abstract: Certain ultrasound features are associated with an increased risk of thyroid malignancy. However, they were studied mainly in papillary thyroid cancers (PTCs); these results cannot be simply extrapolated for the differentiation of follicular thyroid adenomas and cancers (FTAs and FTCs). The aim of our study was to perform a meta-analysis to identify sonographic features suggesting malignancy in the case of follicular lesions, potentially differentiating FTA and FTC. We searched thirteen databases from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 60 publications
(19 reference statements)
1
11
1
1
Order By: Relevance
“…Therefore, we believe that all six systems assessed in this study are effective tools to select FTC for FNA in clinical practice. In fact, previous studies have shown that follicular neoplasms are large [22][23][24][25][26][27]. The mean maximum diameter of FTC (3.9 ± 2.1 cm) in our study was higher than any threshold proposed for ultrasound-based malignancy risk stratification systems.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Therefore, we believe that all six systems assessed in this study are effective tools to select FTC for FNA in clinical practice. In fact, previous studies have shown that follicular neoplasms are large [22][23][24][25][26][27]. The mean maximum diameter of FTC (3.9 ± 2.1 cm) in our study was higher than any threshold proposed for ultrasound-based malignancy risk stratification systems.…”
Section: Discussioncontrasting
confidence: 63%
“…In our study, FNA was considered indicated for 65.3% to 93.1% of all FTAs and for 62.2% to 89.7% of FTAs sized ≤ 4 cm. We believe that this result is mainly due to the large size of follicular neoplasms [22][23][24][25][26][27]. Furthermore, our study showed that the unnecessary biopsy rates with use of "pattern-based" systems were higher than those with use of "score-based" systems irrespective of the lesion size because of the different criteria for determining the indications for biopsy.…”
Section: Discussionmentioning
confidence: 87%
“…An interrupted halo, this significant sonographic characteristic, was confirmed by Kaoru Kobayashi et al 's study 17 which showed that tumor protrusion on ultrasonography was a strongly suggestive finding of FTC. A meta-analysis by Borowczyk et al 18 also suggested that the most crucial characteristic connected with an increased risk of FTC was the tumor protrusion. Our conclusion was also consistent with the studies of Zhang et al 19 and Solbiati et al 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The nodules were classified as C-TIRADS 4A, which were adjusted to one level lower after CEUS found the nodules to be benign. A study reported that ultrasound imaging of this pathological type may misdiagnose nodules as follicular adenoma [ 10 ]. However, careful observation of the capsule after the enhancement of the aforementioned nodules showed intermittent blur.…”
Section: Discussionmentioning
confidence: 99%